Preliminary Study on Citronella Soap Production in Getting Halal Certification in Malaysia - Mazita, Mokhtar; Fernando, Yudi; Azizan, Azit; Wan Khairul Anuar, Wan Abd Manan (2020)
Produce home made soap with creativity own design and natural formula. A good aromatherapy home made soap.